An environmental imperative in the development of the national economy: increasing the potential of microalgae - V. V. Melikhov; L. N. Medvedeva; M. V. Frolova (Юг России: экология, развитие, 2020)
Aim. To study the methodological basis for increasing the potential of applications of microalgae in the national economy, as one of the environmental imperatives in the development of new natural resources for future generations.Materials and Methods. The research was conducted on the basis of content analysis of Russian and foreign scientific publications and materials obtained in the course of expeditions and experimental and sociological research. The clustercognitive approach and economic-mathematical modeling were used for a more complete exposition of the topic.Discussion. According to imperatives of the green economy, environmental technologies will become leading factors in the development of the world economy. The most important incentive for entrepreneurs in the environmental market will be growing the demand of consumers and of governments. Promising areas include the use of microalgae in the production of foods beneficial to human health, feed additives in animal husbandry, poultry farming and fish farming, substances for improving water quality in reservoirs and the clean-up of oil spills. The issue of increasing the potential of microalgae at the regional level on the basis of a cognitive cluster approach is most relevant. The procurement of live microalgae biomass in amounts necessary to thoroughly supply world and national markets remains challenging in both technological and technical terms. Economic and mathematical models and sociological research, as well as the opinions of experts, allow us to justify business decisions in opening microalgae production facilities. Microalgae Chlorella vulgaris and Spirulina platensis present promising prospects for entrepreneurial investment due to the high value of their metabolites.Conclusion. The increase in production and applications of microalgae is of major strategic potential in the development of the national economy, as the manufacture of bio-products and immune-stimulating drugs increases every year in response to climate change, pandemics, environmental pollution, food shortages and difficulties in accessing clean water. It is necessary to adopt legislative and regulatory instruments and organizational measures aimed at stimulating the investment of funding entities and entrepreneurs in the production of microalgae products in various sectors of the economy. International collaborations, industrial enterprises and space agencies (e.g. Roscosmos and NASA) are actively conducting research into the use of microalgae for the processing of organic waste in human living facilities in space as a source of both oxygen and food. The issue of creating clusters and applying mechanisms of public-private partnership aimed at increasing the profitability of bio-product manufacture from microalgae in various industries and sectors of the economy at the macro-and meso-level remains relevant.